Tryptophan degradation enzymes and Angiotensin (1−7) expression in human placenta. (September 2022) - Silvano, Angela; Seravalli, Viola; Strambi, Noemi; Tartarotti, Enrico; Tofani, Lorenzo; Calosi, Laura; Parenti, Astrid; Di Tommaso, Mariarosaria
Abstract: Indoleamine 2, 3-dioxygenase 1 (IDO1) and tryptophan 2, 3-dioxygenase (TDO) are key enzymes for tryptophan degradation, regulating immune tolerance during pregnancy. The intrauterine renin-angiotensin system is also involved in the progression of a healthy pregnancy. Angiotensin(1−7) maintains the integrity of fetal membranes via counteracting the pro-inflammatory actions of Angiotensin II. No data are available on placental Angiotensin(1−7) co-expression with TDO. We aimed to characterize TDO mRNA expression and its localization in different areas of the placenta of physiological pregnancies delivered at term; its co-expression with Angiotensin(1−7) and its correlation with the plasma kynurenine/tryptophan (Kyn/Trp) ratio was investigated. This prospective observational study included a nonconsecutive series of 20 singleton uncomplicated pregnancies delivered vaginally. TDO mRNA was expressed in both maternal and fetal sides of the placentas and TDO protein also in the villi and it was co-expressed with IDO1 in almost half of the placental cells at these sites. The percentage of TDO + and IDO1 + cells appeared to be influenced by maternal pre-gestational smoking and newborn weight. A strong correlation was found between the percentage of TDO + and IDO1 + cells in the villi. TDO + cells also expressed Angiotensin(1−7), with a higher percentage on the fetal side and in the villi compared to the maternal one. Kyn/Trp plasma ratio was not correlated with IDO and TDO expression nor with the patient's characteristics. Collectively, our data indicate that TDO is detectable in placental tissue and is co-expressed with IDO and with Angiotensin(1−7) + on the fetal side and in the villi. Highlights: Tryptophan 2, 3-dioxygenase (TDO) is expressed in healthy human placenta. TDO is found in maternal, villi, and fetal sides of placenta. TDO is co-expressed with IDO1 and Angiotensin (1−7) (Ang 1–7). TDO, IDO1 and Ang(1−7) expression are influenced by pre-gestational smokingand newborn weight. Percentage of TDO + /Ang(1−7) + cells is correlated with maternal age and newborn sex.